Human Resources Development for Agro - Tourism in Mae Tha Sub - district, Mae On District, Chiang Mai Province - Raksathip, Narat-thanan; Thongma, Weerapon (Dusit Thani College Journal, 2020)
This research aims to explore factors that influence the level of potential development of community personnel in agro-tourism management. This research is analyzed based on quantitative analysis, the management theory. The concepts of capacity enhancing and human resource development, have been applied as the research framework. The specified research area is located in Mae Tha sub-district, Mae On district, Chiang Mai Province. Forty-nine key informants have been participated in this research including 14 of administrators and staff who work for Mae Tha Sub-district Administrative Organization, 22 of Mae Tha organic members, and 13 of community leaders. The collecting data method by questionnaire form as well as the descriptive statistics are used to analyze the data. The development of potential personnel for enhancing the capacity of tourism management with the concept of human resources development by KUSAMOC as a tourism management concept is to strengthen the power of the new generation for overall social change. The average means of 7 compositions is 3.97 and that represents a high potential level of the personnel in advanced level of agricultural tourism management. This research found that focusing on individual leads to greatly increase in a collaborative teamwork which is essential for a new generation to deal with social change. Moreover, applying the tourism development strategies to the next generation enhances youths to be an authentically capable leader.